Overview of methods for determining the location of sound sources - Ryaby, M.; Shatokhin, M. (Problems of Informatization and Management, 2025)
The paper provides an overview and systematic comparison of modern methods for sound source localization, including time-based (TDoA, GCC), subspace-based (MUSIC, ESPRIT), beamforming methods, statistical tracking approaches, and neural network and hybrid solutions. For each class of methods, the key advantages and limitations are analyzed, as well as their suitability for use in real acoustic conditions, in particular in the presence of noise, reverberation, and multiple simultaneous sources. Based on a comparative analysis, it is concluded that hybrid architectures that combine physically interpreted features with adaptive machine learning models are the most promising for practical systems. A hybrid concept of multi-source localization is proposed, which uses GCC cross-spectral features and a multi-head neural network model to estimate the number of active sources, their directions, and the confidence of the prediction.